Implementation of Lean Manufacturing to increase productivity in a company in the metal-mechanical sector in northern Lima, 2025 - Gamboa Cárdenas, Adrián Moisés (2026)
This work contributes to Sustainable Development Goal (SDG) 9: Industry, Innovation, and Infrastructure, by promoting the optimization of sustainable industrial processes. The research determined the impact of Lean Manufacturing implementation, using 5S and Value Stream Mapping (VSM) tools, on productivity improvement in a metalworking company located in North Lima, 2025. The study is classified as applied research, with a quantitative approach and explanatory level, and employed a pre-experimental design, with measurements taken before and after the intervention. The study population consisted of perforated metal sheets processed between June and September, with data collected through direct observation, productivity, efficiency, and effectiveness record sheets, and Lean application verification forms. Descriptive and inferential statistical analysis was performed using SPSS v25 software, showing a productivity increase of 47.03%, a relative efficiency improvement of 18.96%, and an effectiveness improvement of 24.69% after the intervention. The statistical results validated the alternative hypothesis, demonstrating that Lean Manufacturing methodology significantly optimized productivity, efficiency, and effectiveness in the production area of the considered metalworking company.